Level of knowledge, awareness and attitude of workers towards the effectiveness Integrated Pest Management (IPM) practices in Rubber Industry Smallholder Development Authority (RISDA) Sekijang, Segamat Johor / Adilah Abu Hassan - Abu Hassan, Adilah (Faculty of Plantation and Agrotechnology, 2015)
The understanding on various aspects of pesticide-use has revealed better awareness in certain aspects and poor understanding in certain others. Pest control practices have been made and this approach has been used either as a defensive measure or treatment. This paper is focused on level of knowledge, awareness and attitudes about Integrated Pest Management (IPM) practices among plantation workers in RISDA Sernaian, Sekijang Segamat Johor. This study used the data collected from a survey among plantation workers using structured questionnaire . A total of one hundred and twenty nine (129) respondents were interviewed in order to obtain a survey on their knowledge, awareness and attitudes about IPM practices. A Likert scale of I to 5 (lrepresenting Strongly Disagree and 5 representing Strongly Agree) was used to measure respondents' knowledge, awareness and attitude related to the practices IPM. In this study, the descriptive analysis, reliability analysis, factor analysis and multiple regressions were applied to analyse the gathered data. The finding indicates that plantation workers mainly have positive attitudes toward implementing rPM practices even though there were problems in implementing the practices. Based on factor analysis three (3) factors were identified to influence plantation workers towards implementing IPM practices . These factors are knowledge, awareness and attitudes of the plantation workers.The reliability analyses were used to determine the internal consistency. Research findings found overall factors showed Cronbach's Alpha is acceptablemeans there are more than 70 per cent. The multiple regression method was used to examine the relationship between set of independent variable and one dependent variable. Research findings revealed that factor of knowledge contributed to the highest significant relationship toward IPM practices with standard coefficient 60.90 per cent and significant value is below than 0.05.There was a need to intensify plantation workers awareness, knowledge and attitudes on Integration Pest Management through many ways from poor understanding and practices about IPM to the successful, to better that towards attaining the sustainable in plantation agriculture sector.